Cognitive impairment in late‐life bipolar disorder is not associated with Alzheimer's disease pathological signature in the cerebrospinal fluid. (15th February 2016) - Forlenza, Orestes V; Aprahamian, Ivan; Radanovic, Márcia; Talib, Leda L; Camargo, Marina ZA; Stella, Florindo; Machado‐Vieira, Rodrigo; Gattaz, Wagner F
Abstract : Objectives: Cognitive impairment is a common feature of late‐life bipolar disorder (BD). Yet, there is limited information on the biological mechanisms associated with this process. It is uncertain whether cognitively impaired patients with BD may present the Alzheimer's disease (AD) bio‐signature in the cerebrospinal fluid (CSF), defined as a combination of low concentrations of the amyloid‐beta peptide (Aβ1‐42 ) and high concentrations of total tau (T‐tau) and tau phosphorylated at threonine 181 (P‐tau). In this study, we sought to determine whether cognitive impairment in elderly patients with BD is associated with the AD CSF bio‐signature. Methods: Seventy‐two participants were enrolled in the study. The test group comprised older adults with BD and mild cognitive impairment (BD‐MCI; n = 16) and the comparison groups comprised patients with dementia due to AD (n = 17), patients with amnestic MCI (aMCI; n = 14), and cognitively healthy older adults (control group; n = 25). CSF samples were obtained by lumbar puncture and concentrations of Aβ1‐42, T‐tau and P‐tau were determined. Results: CSF concentrations of all biomarkers were significantly different in the AD group compared to all other groups, but did not differentiate BD‐MCI subjects from aMCI subjects and controls. BD‐MCI patients had a non‐significant reduction in CSF Aβ1‐42 compared to controls, but this was still higher than in the AD group. Concentrations of T‐tau and P‐tau in BD‐MCI patients were similar to those in controls, and significantly lower than those in AD. Conclusions: Cognitively impaired patients with BD do not display the so‐called AD bio‐signature in the CSF. We therefore hypothesize that cognitive deterioration in BD is not associated with the classical pathophysiological mechanisms observed in AD, i.e., amyloid deposition and hyperphosphorylation of microtubule‐associated tau protein.